Virtual Sacred Spaces and AI-Augmented Pilgrimage Experiences in the Digital Era (International Journal of Latest Technology in Engineering Management & Applied Science, 2026)
BackgroundThe convergence of artificial intelligence, virtual reality, and augmented reality technologies is fundamentally transforming religious practices and spiritual experiences. Traditional pilgrimage, historically requiring physical presence at sacred sites, is being reimagined through immersive digital environments that offer unprecedented accessibility while raising profound questions about authenticity, theological legitimacy, and the nature of sacred experience itself.ObjectiveThis study comprehensively examines the emergence of virtual sacred spaces and AI-augmented pilgrimage experiences, analyzing their technological foundations, spiritual implications, accessibility benefits, ethical challenges, and future trajectories. The research synthesizes current scholarship to understand how digital technologies are reshaping religious tourism, spiritual engagement, and the conceptualization of sacred space in contemporary society.MethodsA systematic literature review was conducted across multiple scholarly databases, yielding 78 unique peer-reviewed publications. The top 30 most relevant studies were analyzed using thematic synthesis, focusing on technological implementations, user experiences, theological perspectives, ethical considerations, and cultural impacts.Studies encompassed diverse religious traditions including Islam, Christianity, Hinduism, Buddhism, and Judaism, examining VR/AR/AI applications in pilgrimage simulation, sacred space reconstruction, and spiritual guidance.ResultsThe analysis reveals that virtual sacred spaces successfully enhance accessibility for individuals facing physical, financial, or geopolitical barriers, with VR technologies demonstrating significant potential for pre-pilgrimage training and cultural preservation. AI-augmented companions provide real-time translation, historical context, and emotional support, deepening engagement with sacred sites.However, critical limitations persist: virtual experiences cannot fully replicate the communal, ritualistic, and transformative elements of physical pilgrimage. Theological perspectives vary significantly across traditions, with concerns about sacramental validity, embodied presence, and the commodification of sacred experiences. User studies indicate positive responses to aesthetic quality and sense of presence, though multisensory integration remains technically limited.ConclusionVirtual sacred spaces and AI-augmented pilgrimage represent complementary rather than replacement technologies for traditional religious practices. They democratize access to sacred sites, preserve cultural heritage, and facilitate interfaith understanding, while simultaneously challenging established theological frameworks. Future development must prioritize ethical design, cultural sensitivity, theological consultation, and enhanced multisensory integration. The field requires interdisciplinary collaboration among technologists, religious scholars, ethicists, and faith communities to ensure these innovations serve spiritual authenticity rather than commercial exploitation.